Protocol: Child and adolescent mental health and psychosocial support interventions: an evidence and gap map of low- and middle-income countries - Sharma, M; Perera, C; Ipince, A; Bakrania, S; Shokraneh, F; Idele, P; Anthony, D; Banati, P (Wiley, 2022)
This is the protocol for a Campbell review. The objective of this evidence and gap map is to provide an overview of the existing evidence on the effectiveness of interventions aimed at promoting mental health and reducing or preventing mental health conditions among children and adolescents in low- and middle-income countries.